ADAPTASI PERILAKU SISWA SMA DALAM SITUASI ANOMI - Ronasti, Desi; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Schools as formal educational institusions take roles and responsibilities in instilling social values and norms in order to shape the charahter and personality of students. the meeting and mixing of the environment around culture in a totality in such a way that certain behaviours are formed at school or the educational environment is considered part of cultural milieu.  The sociology of education views the symptomps of education as part of the social structure of society.  Social, economic, cultural and academic differences found in schools make students find it difficult to socialize with each other.  This study aims to determine the limitations of students in schools in academic, economic and social limitation it faces next to determine the adaptation of student bahaviour in academic, economic and social limitationit faces and to determine the effect of academic, economic and social constrains on the adaptation of student behavior in school.  The method used is quantitative where by quantitative inferential method.  In the sampleselection used probability sampling (cluster area sampling) techniques with a total number of respondents as many as 154 respondents.  The result of this study stated that academic, economic and social limitations perceived by high school students tend to be still limited in achieving the goals or demands that exist in school. Adaptation of student behavior found in the field is largely conformity meaning students are able to adapt after facing perceived limitations. From the results of the analysis of the correlation between academic, economic and social limitations to behavioral adaptation is 0. 553 which means it has a moderate relationship. Key Words: Anomie, Behavioural adaptation, High school student